Coexistence of Wireless Avionics Intra-Communication Networks - Mersch, Steffen; Meyerhoff, Thomas; Kruger, Leo; Timm-Giel, Andreas (2018 6th IEEE International Conference on Wireless for Space and Extreme Environments (WiSEE), 2018)
Modern passenger aircraft include an increasing number of sensors and actuators that today use wires for data transmission. Wireless Avionics Intra-Communication (WAIC) networks offer an opportunity to reduce the wiring harness complexity of aircraft. In contrast to wired communications, interference from other radio systems has to be expected when using wireless communications. Consequently, appropriate measures must be applied to guarantee performance required by the applications using a WAIC network. This paper discusses the coexistence of WAIC networks operated on board of different aircraft in mutual radio range. The WAIC networks under consideration use a Time-Division Multiple Access (TDMA) scheme in combination with channel hopping for medium access and Automatic Repeat Request (ARQ) to compensate for packet losses caused by interference. The ability of these networks to coexist is examined with regard to the requirements of applications suited for WAIC.